IMPROVING STUDENTS WRITING DESCRIPTIVE TEXT OF GRADE VII AT SMP N 2 TOLITOLI BY USING PICTURES - Ismail Yunus H (Universitas Madako Tolitoli, 2018)
This research objective was to prove that whether of the use of pictures can improve students writing descriptive test or not. The design of this research was pre-experimental research. The sample of the research was the seventh grade students that consisted of 27 students. They were grade VIIA of SMP Negeri 2 Tolitoli. The data obtained from pre-test, treatment and post-test. The researcher gave pre-test and post-test to know students previous ability in writing descriptive text. The result of the data analysis showed that pictures contributed greatly to the students writing descriptive text. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test was 36.41 while in the post-test improved up to 68.52. The data of this research were analyzed by using SPSS program version 16.0. The Minimum Mastery Criterion of English lesson was 75 (seventy-five). Then the data of both tests were analyzed by using T-test, and result showed that the T-test value 18.43 was high than T-table value 2.056 . The result indicates that there was an improvement in writing descriptive text by using pictures. It can concluded that teaching writing descriptive text by using pictures is effective to improve students writing descriptive text.Keywords : Writing, Descriptive text, Pictures.